Evolutionary lags in the primate brain size/body size relationship revisited - R. I. M. Dunbar (PLoS ONE, 2026)
The original brain lag hypothesis proposed that primate brain evolution depended on spare energy derivative of savings of scale enabled by first increasing body size. However, in a seminal analysis, Deaner & Nunn concluded that there was no evidence for a brain lag. I revisit their analysis and show that using statistically more appropriate analyses and updated data yields a significant brain lag effect. However, contrary to the original brain lag hypothesis, the brain/body ratio does not converge back on the allometric regression line, but continues to evolve beyond it. Increases in brain size are correlated with exploiting large group size rather than large body size as the principal defence against predation risk, with significant growth in brain size (but not body size) only being possible if species adopt a more frugivorous diet. I then use these findings to show that hominins followed a similar trajectory from an australopithecine baseline on the relevant allometric regression. In sum, the brain lag effect is much more complicated than the original hypothesis proposed, with a distinctive switch from emphasising body size to brain size (hence group size) as a solution to ecological challenges.